Analyzing Recent Trends of Financial Statement in Commercial Banks: A Comparative Analysis of Asset Ratios in Government and Private Banks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Development of a country mostly depends upon the financial structure provided by the commercial banks. The responsibility of banks in the developing country like ours is crucial and significant. The financial position of the banks is more or less concurrent with their working capital and fixed assets. Where the coefficient correlation between the working capital and fixed assets are in a positive side the position is considered good.For our study we have taken into consideration one nationalized bank and two private banks, as after liberalization, the private commercial banks have evolved and are functioning at par with the government banks under the guidance of Reserve Bank of India. The researchers have chosen these three banks as they are listed in both NSE BSE Index. The purpose of this study is to find out, how far private banks are maintaining the ratio of their assets as well as their working capital as compared to the government banks. In support of this intention a relative study is conducted by choosing five years data from 2009 to 2013 of SBI, HDFC, ICICI banks.